LINGKUNGAN KERJA FISIK DAN NON FISIK TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Barus, Ilham Andariasta (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2025)
This study aims to determine whether the physical work environment has a direct effect on employee performance at PTPN III Medan. Does the physical work environment affect employee performance through job satisfaction at PTPN III Medan. Does the non-physical work environment have a direct effect on employee performance at PTPN III Medan. Does the non-physical work environment affect employee performance through job satisfaction at PTPN III Medan. The population in this study was 310 people and 175 samples were taken using the Slovin method. The analysis technique used is Path Analysis. The results showed that the physical work environment had a positive and significant effect on job satisfaction at PTPN III Medan. Non-physical work environment has a positive and significant significant effect on job satisfaction at PTPN III Medan. Physical work environment has a positive and significant effect on employee performance at PTPN III Medan. Non-physical work environment has a positive and significant effect on employee performance at PTPN III Medan. Job satisfaction has a negative and insignificant effect on employee performance at PTPN III Medan. Job satisfaction has a positive and significant direct effect between the physical work environment on employee performance at PTPN III Medan. Job satisfaction has a positive and significant direct effect between non-physical work environments on employee performance at PTPN III Medan.